Bayesian estimation of the true prevalence of Mycobacterium avium subsp. paratuberculosis infection in Cypriot dairy sheep and goat flocks - Liapi, M.; Leontides, L.; Kostoulas, P.; Botsaris, George; Iacovou, Y.; Rees, C.; Georgiou, K.; Smith, G. C.; Naseby, D. C. (My University, 2011)
We estimated the prevalence of Mycobacterium avium subsp. paratuberculosis (MAP) infected sheep and goats, older than 2 years, reared in the region effectively controlled by the Government of the Republic of Cyprus, in September 2005. The sera collected from 8011 animals (3429 sheep and 4582 goats) from 83 flocks, non-vaccinated against MAP, were examined for antibodies with a commercially available enzyme linked immunosorbent assay (Pourquier® paratuberculosis antibody screening ELISA). The true prevalence of MAP infection was calculated, in a Bayesian framework, separately in sheep and goats, with models that adjusted for the misclassification of animals because of the imperfect accuracy of the ELISA. The within-flock mean seroprevalence in sheep and goats was 9.9% (95% CI: 8.9; 10.9%) and 7.9% (7.2; 8.7%), respectively. There was at least one seropositive sheep in 52% (38; 66%) of flocks with sheep and one seropositive goat in 50% (39; 62%) of flocks with goats. Within the seropositive flocks the mean seroprevalence was 12.1% (10.9; 13.4%) and 10.3% (9.3; 11.4%) in sheep and goats, respectively. The calculated mean true prevalence of infected sheep and goats was 15.0 and 11.1%, respectively. There was at least one infected sheep in 60.8% (95% credible interval: 42.3; 78.8%) and at least an infected goat in 48.6% (30.4; 68.5%) of the flocks. In the infected flocks, the mean within flock true prevalence of infection in sheep and goats was estimated at 24.6% (16.3; 33.3%) and 23.1% (15.5; 33.6%), respectively. © 2010 Elsevier B.V.
Keywords: Bayesian estimation; ELISA; Mycobacterium avium paratuberculosis; Seroprevalence; True prevalence